2023
DOI: 10.3390/ph16070989
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Albizia lebbeck (L.) Benth. Leaf Extract against Glutamate-Induced Endoplasmic Reticulum Stress and Apoptosis in Human Microglial Cells

Abstract: Endoplasmic reticulum (ER) stress caused by excessive glutamate in the central nervous system leads to neurodegeneration. Albizia lebbeck (L.) Benth. has been reported to possess neuroprotective properties. We aimed to investigate the effect and mechanism of A. lebbeck leaf extracts on glutamate-induced neurotoxicity and apoptosis linked to ER stress using human microglial HMC3 cells. A. lebbeck leaves were extracted using hexane (AHE), mixed solvents, and ethanol. Each different extract was evaluated for cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Previous research has shown that extracts of A. lebbeck leaves can inhibit neuronal cell death 25 . In this study, we aimed to assess the inhibitory potential of ALE against glutamate-induced hippocampal neuronal cell death.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research has shown that extracts of A. lebbeck leaves can inhibit neuronal cell death 25 . In this study, we aimed to assess the inhibitory potential of ALE against glutamate-induced hippocampal neuronal cell death.…”
Section: Resultsmentioning
confidence: 98%
“…The edible part of the A. lebbeck leaves was separated and washed with deionized water according to the procedure described by Phoraksa and colleagues 25 . Briefly, A. lebbeck leaves were boiled for 2 min, followed by homogenization using an electric blender.…”
Section: Methodsmentioning
confidence: 99%